TATA KELOLA ADMINISTRASI PENANGANAN PERKARA DAN KADERISASI PADA ORGANISASI BANTUAN HUKUM DIKAITKAN DENGAN ACCESS TO JUSTICE DI WILAYAH DAERAH ISTIMEWA YOGYAKARTA - Harahap, Zairin; Wulansari, Retno (Jurnal Yuridis, 2017)
Research on administrative management of case handling and cadre forming on legal aid organization is related to access to justice in Yogyakarta Special Region aimed to know the system of cadre forming, management and inhibiting factor of free legal aid funding for the poor. This type of research is empirical juridical with qualitative descriptive analysis method The result of this research is pattern of cadre forming in legal aid organization in using system designed independently by each legal aid organization. The management of case handling in the legal aid organization uses internal rules that are prepared independently in each OBH. The inhibiting factor in the provision and legal aid services of legal aid organization is the inability of justice seekers in completing the administrative requirements that is required by the Ministry of Justice and Human Rights and the lack of socialization to the community regarding free legal aid services. The formulated suggestion is the formation of cadre pattern standardization on legal aid organization. Case handling management of legal aid organization should be developed using standard operational procedure. In overcoming the inhibiting factors in the provision and legal assistance services of legal aid organization. The Ministry of Justice and Human Rights Regional Office should undertake more massive efforts in the socialization of legal aid and simplify the rules on administrative files of free legal aid services for the poor.